ANT 2012/13: AWI airborne Accumulation Radar data over DML focusing on the Sør Rondane Mountains, Halvarryggen, Jutulstraumen Glacier, and south of EDML (GEA, WEGAS, MaBaJu, and RECISL Projects) - Daniel Steinhage; Angelika Humbert; Wilfried Jokat; Veit Helm (PANGAEA, 2025)
This dataset contains airborne radar data acquired using the AWI Accumulation Radar (ACCU) system during the Antarctic season of 2012/13. The profiles cover DML focusing on the Sør Rondane Mountains, Halvarryggen, Jutulstraumen Glacier, and south of EDML over the Slessor and Recovery Ice Streams. The data are available as netCDF files (including waveforms and metadata), KML files of the profile line locations, and quicklook images of the radargrams.